The reflux phase in monetary circuit theory and stock-flow consistent models - Edouard Cottin-Euziol; Hassan Bougrine; Louis-Philippe Rochon (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2024)
Stock-flow consistent (SFC) modelling and monetary circuit theory (MCT) have many similarities. However, an important difference concerns the reflux phase, during which the credits issued by banks are repaid. This phase is constitutive of MCT models, but does not generally appear explicitly in SFC models. The authors propose here to develop an SFC model in which the bank loans issued at the beginning of a period are explicitly repaid at the end of it. The repayment of long-term bank loans financing investments will then represent a leakage outside the monetary circuit and affect the level of aggregate demand and the dynamics of the model. The authors show that considering these repayments could have a lasting effect on corporate profits, corporate indebtedness, and growth of production. This result suggests that it could be interesting to focus more on the reflux phase within SFC models, taking inspiration from MCT.
Keywords: E11; E12; E17; 330; Monetary circuit; Stock-flow consistency; Reflux; Bank loans